2023
DOI: 10.3847/1538-4357/ad0972
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution and Nuclear Structure in the Dwarf Galaxy POX 52 Studied by Multiwavelength Data from Radio to X-Ray

Taiki Kawamuro,
Claudio Ricci,
Satoshi Yamada
et al.

Abstract: The nearby dwarf galaxy POX 52 at z = 0.021 hosts an active galactic nucleus (AGN) with a black hole (BH) mass of M BH ∼ 105–6 M ⊙ and an Eddington ratio of ∼0.1–1. This object provides the rare opportunity to study both AGN and host-galaxy properties in a low-mass highly accreting system. To do so, we collected its multiwavelength data from X-ray to radio. First, we construct a spectral energy distribution, and by fitting it with AGN and host-galaxy compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 176 publications
1
0
0
Order By: Relevance
“…Specifically, hints of star formation quenching induced by AGN feedback (Penny et al 2018) and lower-thanexpectation global HI content (Bradford et al 2018) have both been reported in dwarf galaxies with AGN. Similar evidence on such feedback is also seen in several of the latest observational studies (Davis et al 2022;Kawamuro et al 2024;Yang et al 2023). From the theoretical perspective, analytic analysis (e.g., Silk 2017; Dashyan et al 2018) and new simulations (e.g., Koudmani et al 2019Koudmani et al , 2021Lanfranchi et al 2021) have all pointed out the possibly significant effects of AGN feedback in dwarfs.…”
Section: Introductionsupporting
confidence: 64%
“…Specifically, hints of star formation quenching induced by AGN feedback (Penny et al 2018) and lower-thanexpectation global HI content (Bradford et al 2018) have both been reported in dwarf galaxies with AGN. Similar evidence on such feedback is also seen in several of the latest observational studies (Davis et al 2022;Kawamuro et al 2024;Yang et al 2023). From the theoretical perspective, analytic analysis (e.g., Silk 2017; Dashyan et al 2018) and new simulations (e.g., Koudmani et al 2019Koudmani et al , 2021Lanfranchi et al 2021) have all pointed out the possibly significant effects of AGN feedback in dwarfs.…”
Section: Introductionsupporting
confidence: 64%